EFFECT OF DIFFERENT GROWING MEDIAS MIXTURE ON GERMINATION AND SEEDLINGS GROWTH OF MANGO (MANGIFERA INDICA L.) CULTIVARS UNDER NET HOUSE CONDITIONS - J. S. PARASANA; H. N. LEUA; N. R. RAY (The Bioscan, 2013)
Mango is important fruit crop in India. If grow scientifically it is the highest remunerative fruit crop. Therefore present investigation was undertaken to increased better germination and growth of mango cultivars. The present investigation entitled “Effect of different growing medias mixture on germination and seedlings growth of mango (Mangifera indica L.) cultivars under net house conditions”. From the foregoing discussion it can be concluded that among the different growing medias M3 i.e. Soil + Sand + Farm Yard Manure (2: 1: 1) is found to be the most effective for better germination of mango stone as well as growth of mango seedlings (height, number of leaves, length of root and shoot, stem girth, fresh and dry weight of seedlings as well as survival per cent of seedlings). Similarly among the cultivars tried, V3 (LSM–12-Master Royal) found better for the above parameters. Therefore, the combination of M3V3 (Soil + Sand + Farm Yard Manure (2: 1: 1) + LSM-12-Master royal) found most suitable for growing of mango stone for rootstock purpose under nursery conditions.